# Solution to a change-of-basis theoretical problem

Consider the following problem.

Let $$V$$ be an $$n$$-dimnensional $$\mathbb{K}$$-vector space and let $$\textbf{A} \in \mathbb{K}^{n\times n}$$ be an invertible matrix. Show that there are basis $$B_1, B_2$$ such that $$\textbf{A}$$ is the change of basis matrix from $$B_1$$ to $$B_2$$.

I found this problem, elementary as it may be, quite challenging, since in attempting to solve it I found I had several misconceptions on the theory of linear algebra. For now, I would like to know if my following approach is correct. I will also leave the theoretical comments I made when reasoning on the problem, since that may reveal any flaws either in my understanding or my procedure.

$$~$$

I : Let $$B_2 = \{\beta_1, \ldots, \beta_n\}, B_1 = \{\alpha_1, \ldots, \alpha_n\}$$ be two basis of $$V$$. We know there are scalars such that

\begin{align*} &\alpha_1 = x_1^{(1)}\beta_1 + \ldots + x_n^{(1)}\beta_n \\ &\ldots \\ &\alpha_n = x_1^{(n)}\beta_1 + \ldots + x_n^{(n)}\beta_n .\end{align*}

and that they define a unique transformation matrix

\begin{align*} \textbf{T}_{B_1 \to B_2} = \begin{pmatrix} x_1^{(1)} & \ldots & x_1^{(n)} \\ \ldots \\ x_n^{(1)} & \ldots & x_n^{(n)} \end{pmatrix} .\end{align*}

$$~$$

II : Let $$(\lambda_1, \ldots, \lambda_n)_{B_1}$$ be the representation of a vector $$\textbf{v} \in V$$ under basis $$B_1$$. We know

\begin{align*} &(\lambda_1, \ldots, \lambda_n)_{B_1} \equiv (\delta_1, \ldots, \delta_n)_{B_2} \\ \iff & \lambda_1 \alpha_1 + \ldots + \lambda_n \alpha_n = \delta_1 \beta_1 + \ldots + \delta_n \beta_n .\end{align*}

III : Consider the equation

\begin{align*} \textbf{A}\begin{pmatrix} \lambda_1 \\ \vdots\\ \lambda_n \end{pmatrix} &= \begin{pmatrix} \delta_1\\\vdots\\ \delta_n \end{pmatrix} .\end{align*}

Since $$\textbf{A}$$ is invertible, this equation has a solution. Particularly, such solution is given by

\begin{align*} \begin{pmatrix} \lambda_1\\ \vdots\\ \lambda_n \end{pmatrix} &= \textbf{A}^{(-1)}\begin{pmatrix} \delta_1\\ \vdots\\ \delta_n \end{pmatrix} \\ &= \begin{pmatrix} a_{11}\delta_1 + \ldots + a_{1n}\delta_n \\ \ldots & \\ a_{n1}\delta_1 + \ldots + a_{nn}\delta_n\end{pmatrix} .\end{align*}

In other words, for any $$\textbf{v} = (\delta_1, \ldots, \delta_n)_{B_2}$$, we can find a vector with coordinates in $$B_1$$ whose linear transformation via matrix $$\textbf{A}$$ maps to the coordinates $$(\delta_1, \ldots, \delta_n)$$. We can also atest the coordinates of such vector are of the form

\begin{align*} \Big(\sum_{n=1}^{\infty} a_{1i}\delta_i, \ldots, \sum_{n=1}^{\infty} a_{ni} \delta_i \Big) .\end{align*}

where $$a_{ij}$$ is an entry of $$\textbf{A}^{(-1)}$$.

• To clear one thing, your point $2$ implies that if the coefficients of $v\in V$ in $B_1$ are equal to the coefficients of $w\in V$ in $B_2$, then, $v=w$? Jan 7, 2023 at 0:27
• What if you just take $B_1$ to be the standard basis? Jan 7, 2023 at 3:54

To make the theoretical view point clearer let us illustrate with a simple example in $$\mathbb R^2$$.
If you have two basis related say $$c_1=4b_1+6b_2,$$ $$c_2=3b_1+5b_2.$$ then the associated matrix is $$A=\left[\begin{array}{cc}4&3\\6&5\end{array}\right]$$.
But if is added information of how the 1st basis is expressed in the canonical basis, say $$b_1=e_1+3e_2,$$ $$b_2=3e_1+e_2,$$ then the associate matrix is $$B=\left[\begin{array}{cc}1&3\\3&1\end{array}\right]$$.
So, subbing this there above, you get $$c_1=4(e_1+3e_2)+6(3e_1+e_2),$$ $$c_2=3(e_1+3e_2)+5(3e_1+e_2),$$ which upon simplification, you'll have $$c_1=22e_1+18e_2,$$ $$c_2=18e_1+14e_2,$$ with matrix $$C=\left[\begin{array}{cc}22&18\\18&14\end{array}\right]$$.
Observe that $$BA=C$$ then $$A=B^{-1}C$$.